Experiences of Reproductive Coercion in Queensland Women - Price, Elizabeth (Journal of interpersonal violence, 2022)
Reproductive coercion is any interference with a person?s reproductive autonomy that seeks to control if and when they become pregnant, and whether the pregnancy is maintained or terminated. It includes sabotage of contraceptive methods and intervention in a woman?s access to health care. Our study sought to explore the prevalence and associations with reproductive coercion within Queensland, Australia, where legislation addressing domestic violence and abortion are largely state based and undergoing a period of law reform. The study was a retrospective analysis of 3,117 Queensland women who contacted a telephone counseling and information service regarding an unplanned pregnancy. All data were collected by experienced counselors regarding circumstances within a current pregnancy between January 2015 and July 2017. Overall, experience of current domestic violence was significantly more likely to co-occur with reproductive coercion (21.1%) compared with reproductive coercion identified in the absence of other domestic violence (3.1%). Furthermore, significantly more mental health issues were reported by 36.6% of women affected by reproductive coercion, compared with 14.1% of women with no reproductive coercion present. Disclosure for reproductive coercion, violence, and mental health issues was much higher among women who made a repeat contact to the counselors about their pregnancy (17.8%) compared with those who disclosed at first contact (5.9%). These findings demonstrate the importance for health services to ensure that appropriate screening (and re-screening) for reproductive coercion is completed as a distinct part of screening for violence during a health care relationship.